A Multi-Phase Brushless Direct Current Motor Design and Its Implementation in Medium-Altitude Long-Endurance Unmanned Aerial Vehicles - Kurt, Emre; Arabul, Ahmet Yigit; Arabul, Fatma Keskin; Senol, Ibrahim (MDPI, 2024)
Nowadays, electric propulsion system implementation in vehicles is popular, and many studies and prototypes have been accomplished in this field. Aircraft are important members of the vehicle family, and Unmanned Aerial Vehicles (UAVs) are part of this family as well. Some UAVs still have conventional propulsion systems, which are less efficient and are harmful to the environment. In addition, conventional systems are vulnerable to faults in their propulsion system components. To overcome these problems, we designed a multi-phase Brushless Direct Current (BLDC) motor, to achieve fault-tolerant operation. Our designed BLDC motor was implemented in a UAV model that was created on MATLAB Simulink, based on a currently used UAV. Our design and performance analysis are shown for the BLDC motor, both standalone and as implemented in the created UAV model. The electric propulsion system performance is shown, according to the determined flight profile. We observed that the designed electric machine is capable of producing the required torque to create thrust for lifting the UAV. There are some advantages and disadvantages to using the designed electric machine in this class of UAV. This is shown in the related sections.
Keywords: permanent magnet electric machines; electric propulsion system design; unmanned aerial vehicles; Chemistry; Engineering; Materials Science; Physics